Perancangan PC Game First Person Shooter Menggunakan Unreal Development Kit - Rizka Lukmana Afif; Kodrat Iman Satoto; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2014)
The development of hardware increasing rapidly has made game developers take advantage of a variety of new resources that can improve their games. Epic games is a mature game developer who managed to make thousands game and delivered to the hands of gamers . A game engine called Unreal Engine is a big secret behind the success of Epic Games . The game engine is free if you just want to learn or just want to create a personal project and the game is not to be in comercial purposes . It is unfortunate that many students don’t even know of the existence of unreal engine , most of them make use of simpler game engine like game maker , rpg maker , fps creator , and so on. Though unreal engine is superior in any aspect other than the game engine , be it graphics , tools , mechanisms of development , flexible in export-import assets , etc . Based on this information , the author had the idea to make a first person shooter game using the unreal engine as the engine game. Before doing the develpment process, the next step is studying the literature of unreal engine and other supporting software such as 3d studio max to create 3D assets , adobe flash to create the menus , adobe photoshop to create a 2D texture and speedtree assets to create the foliage elements . The next thing is to go into the design phase of scenarios , maps, missions , characters and items that will be placed in the game. The next stage is the development and testing phase to test the game that has finished .The results of the design of this game is the realization of a first person shooter game application using unreal engine with features that can support the player 's interest in playing the game . It’s also introducing unreal engine to students who are interested in designing games.